PENGARUH PENERIMAAN PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI PROVINSI DKI JAKARTA - Erni Yulianti; Muhamad Surya; Dian Sulistyorini Wulandari; Selfiani; Muhammad Ahmi Husein (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2021)
This study aims to determine the effect of Regional Tax Revenue on Regional Original Income (PAD) in DKI Jakarta Province. The variable that is the focus of this research is Local Tax Revenue (X) as the independent variable on Local Original Income (Y) as the dependent variable. The data taken in this study were obtained from the Central Statistics Agency (BPS) DKI Jakarta in the form of a report on the realization of Regional Original Revenue. This study uses a simple linear regression method with correlation coefficient test, coefficient of determination test, linearity test and significance test (t test). The results of this study indicate that Regional Tax Revenue has an effect on Regional Original Income in DKI Jakarta Province with a coefficient of determination R2 of 0.992 or 99.2%. Regional Tax Revenue has a positive correlation (correlation) of 0.996 or 99.6%. From the linearity test model: 0.00 < 0.05 then Ho is rejected, which means that a simple linear regression model can be used to predict the Regional Original Income which is influenced by Regional Taxes. The significant test (t test) shows a significant level of tcount = 19.096 > ttable = 3.182 meaning that local tax revenues have a significant effect on Regional Original Income (PAD), it can be concluded that the addition of Regional Taxes has a positive and significant effect on the addition of Regional Original Income.